Scleral Cross-Linking Using Riboflavin UVA Irradiation for the Prevention of Myopia Progression in a Guinea Pig Model: Blocked Axial Extension and Altered Scleral Microstructure - Liu, Shuai (PLoS One, 2016)
PURPOSE: To develop methods of collagen cross-linking (CXL) in the sclera for the treatment of progressive myopia and to investigate the biomechanical and histological changes that occur in as a result. METHODS: Twenty 14-day-old guinea pigs were divided into 3 groups: the cross-linking group (CL, n = 8), non cross-linking group (NCL, n = 8), and control group (n = 4). The scleras of the right eyes of the guinea pigs in the CL group were surgically exposed and riboflavin was dropped onto the irradiation zone for 20 seconds prior to ultraviolet-A (UVA) irradiation. The same procedure was conducted on the NCL group but without UVA irradiation. No procedure was conducted on the control group. The right eyes of the guinea pigs in the CL and NCL groups were then fitted with -10.00DS optics for six weeks. Retinoscopy and the axial lengths (AXL) were measured at baseline, and at the second, fourth and sixth weeks post-treatment in all three groups. All animal subjects were euthanized after the sixth week and then biomechanical and histopathological examinations of the scleras were conducted. RESULTS: The mean AXL of the NCL group was longer than both the control and CL groups at six weeks (P = 0.001). The mean refractive error in the NCL group was statistically significantly more negative than both the control and the CL groups at six weeks (P = 0.001). The scleral collagen fiber arrangements of the CL and control groups were denser and more regularly distributed than the NCL group. Ultimate stress of the sclera was lowest in the NCL group, followed by the CL then the control group (P<0.05). Ultimate strain (%) of the sclera was lowest in the CL group followed by the NCL and then the control group (P<0.05). CONCLUSION: Our study demonstrates that scleral CXL using riboflavin UVA irradiation effectively prevents the progression of myopia by increasing scleral biomechanical strength in a guinea pig model.